1998
DOI: 10.1093/emboj/17.16.4572
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional solution structure of the 44kDa ectodomain of SIV gp41

Abstract: The solution structure of the ectodomain of simian immunodeficiency virus (SIV) gp41 (e-gp41), consisting of residues 27-149, has been determined by multidimensional heteronuclear NMR spectroscopy. SIV e-gp41 is a symmetric 44 kDa trimer with each subunit consisting of antiparallel N-terminal (residues 30-80) and C-terminal (residues 107-147) helices connected by a 26 residue loop (residues 81-106). The N-terminal helices of each subunit form a parallel coiled-coil structure in the interior of the complex whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
448
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(483 citation statements)
references
References 64 publications
33
448
2
Order By: Relevance
“…No NAbs directed to gp41 were elicited with these immunogens lacking the MPER segment. In addition, when gp41 and its truncated fragments containing the MPER were used as immunogens, we found that such fragments formed either insoluble or soluble aggregates, consistent with other reports [51,70,76,77]. Not surprisingly, it is difficult to obtain conformationally relevant antibodies against MPER in the context of such aggregated proteins.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…No NAbs directed to gp41 were elicited with these immunogens lacking the MPER segment. In addition, when gp41 and its truncated fragments containing the MPER were used as immunogens, we found that such fragments formed either insoluble or soluble aggregates, consistent with other reports [51,70,76,77]. Not surprisingly, it is difficult to obtain conformationally relevant antibodies against MPER in the context of such aggregated proteins.…”
Section: Discussionsupporting
confidence: 90%
“…This may be explained by the fact that the non-covalent interaction of gp120 with gp41 is labile and CD4 binding to gp120 stimulates further shedding of gp120 from the functional envelope spike. Upon dissociation from gp120, gp41 assumes a post-fusion state [70] with concomitant exposure to the immune system of gp41 surfaces that are occluded in the context of the functional trimer, favoring antibody response to irrelevant epitopes [50,71,72].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the decline in NC-1 MAb binding and increase in 5-helix binding is due to the dissociation of prehairpin trimers into gp41 monomers (11,16,36). To test this hypothesis, we used the peptide N36 Mut(e,g) , which was designed to completely abolish any N-helical binding to the C-helical region while maintaining the ability to self-associate into well-defined trimers (16).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…the thermostable 6-helix bundle (8)(9)(10)(11), which drives the membrane merger and eventual fusion (12). In addition to structural information, a wealth of HIV Env-mediated fusion data, which includes inhibition by peptides that mimic the sequences of the N-and C-helical regions (13)(14)(15)(16)(17)(18)(19)(20)(21) and fusion kinetics (22), has lent credence to this model.…”
mentioning
confidence: 98%
“…Concerning the structural information for the loop, FP and TM domains of the viral protein, Caffrey et al presented a model for the structure of the HIV-1 gp41 loop [132], which is based on the solution structure of the SIV gp41 ectodomain [133]. The resulting model presents the first structural information for the HIV gp41 loop, which has been implicated to play a direct role in binding to gp120 and C1q of the complement system.…”
Section: Gp41mentioning
confidence: 99%